Regulation of phage therapy medicinal products: developments, challenges, and opportunities - Fuerst-Wilmes, Miriam; Respondek, Vanessa; Schramm, Michael; Lilienthal, Nils; Buss, Katrin; Duechting, Anja (Frontiers in Cellular and Infection Microbiology, 2025)
Due to their biological properties, bacteriophages represent a regulatory specialty and, at the same time, a challenge with regard to medicinal product approval. Established European guidelines on pharmaceutical quality, preclinical development, and clinical development are only partially applicable. The growing threat posed by infections with multidrug-resistant bacteria has not only boosted the development of bacteriophages for the treatment of bacterial infections in recent years but has also led to substantial progress in adapting regulatory requirements. In 2024, harmonized quality criteria for phage therapy medicinal products and active substances were implemented for the first time in the European Pharmacopoeia. Future European pharmaceutical legislation and recent national acts such as the German Medical Research Act are intended to enable exemptions that address the specific characteristics of phage therapeutics and open new regulatory pathways. Increasing amounts of data on clinical use of phage therapeutics are being published; however, the anticipated breakthrough in the form of a demonstration of efficacy in randomized controlled clinical trials has not yet been achieved. Growing experience with innovative phage preparations has been utilized to adjust regulatory requirements. On the path to approval of a defined phage therapy medicinal product, the evidence-based demonstration of efficacy and safety in randomized controlled clinical trials is the next and decisive step.